2021
DOI: 10.1186/s12889-021-12270-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational program based on theory of planned behavior on promoting nutritional behaviors preventing Anemia in a sample of Iranian pregnant women

Abstract: Background Iron deficiency anemia (IDA) is one of the most common problems during pregnancy. The aim of this research was to determine the effect of educational program based on Theory of Planned Behavior (TPB) on promoting nutritional behaviors preventing anemia in a pregnant woman in Shiraz city, Iran. Methods This quasi-experimental study was done on 150 pregnant women (75 experimental and 75 control groups) who were selected using randomly samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to Mamo et al, understanding the benefits of behaviors played a role in sustainable adherence to performing the behaviors [ 42 ]. Other studies have approved this issue, expressing that a positive attitude toward the behavior could be an effective component of adherence to the behavior [ 43 , 44 ]. Meanwhile, the study of Park and Oh marked that students' attitude toward the behavior had no significant effect on their intention to perform prevention behaviors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Mamo et al, understanding the benefits of behaviors played a role in sustainable adherence to performing the behaviors [ 42 ]. Other studies have approved this issue, expressing that a positive attitude toward the behavior could be an effective component of adherence to the behavior [ 43 , 44 ]. Meanwhile, the study of Park and Oh marked that students' attitude toward the behavior had no significant effect on their intention to perform prevention behaviors [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the main reason why it is necessary to strengthen the role of community medicine to reach the vulnerable or even marginalized sub population [27]. A communitybased intervention designed for maintaining and even improving case detection and screening effort, referral and up to follow-up commonly found anemia and other non-communicable illnesses amongst pregnant and or postpartum women should be conducted massively through community based antenatal care and health promotion [28][29][30].…”
Section: Sociologicalmentioning
confidence: 99%
“…By (Ahmad et al, 2022), using a randomized cluster control study method, research conducted from October 2020 to March 2021 at the Darul Imarah Health Center in Aceh Besar District during the covid 19 pandemic showed that a structured education program for mothers during Pregnancy could improve the application of nutrition practices and health to prevent Anemia and KEK during Pregnancy. 11 Based on this background, the authors are interested in knowing how anaemia and nutrition education influence knowledge, subjective norms, attitudes, perceived behaviour control and intentions on haemoglobin levels in anaemic pregnant women in primary care during the Covid-19 pandemic (Khani Jeihooni, Rakhshani, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%